Explorating Keywords in Technology Adoption Literature with Vos-Viewer - Silvina Husnah; Sri Andriani; Sulis Rochayatun (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
Adoption at the macro level using a bibliometric approach with the aid of VOSviewer